2022
DOI: 10.1016/j.ijchp.2021.100277
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Generalization Meta-Analysis of the Padua Inventory-Revised (PI-R)

Abstract: Background/Objective: The Padua Inventory-Revised (PI-R) is a widely applied instrument to measure obsessive-compulsive symptoms in clinical and nonclinical samples. We conducted a reliability generalization meta-analysis on the PI-R. Method: An exhaustive literature search yielded 118 empirical studies that had applied the PI-R, from which 30 studies (33 samples) reported an original reliability estimate. Results: Assuming a random-effects model, the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The FOCI showed an average reliability of 0.826 for the Symptom Checklist subscale and 0.882 for the Symptom Severity subscale, whereas the C-FOCI showed an average reliability of 0.740 for the Symptom Checklist subscale and 0.794 for the Symptom Severity subscale. Acording to Cicchetti (1994) Compulsive Scale (López Nicolás et al, 2021;López-Pina et al, 2015;Núñez-Núñez et al, 2022;Rubio-Aparicio et al, 2020;Sánchez-Meca et al, 2011, we see that they have similar or slightly better psychometric properties. Nonetheless, we want to again emphasize that the FOCI and C-FOCI are the only OCD scales that briefly examine both OCD symptoms and their severity, while also being brief, simple, and self-reported.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The FOCI showed an average reliability of 0.826 for the Symptom Checklist subscale and 0.882 for the Symptom Severity subscale, whereas the C-FOCI showed an average reliability of 0.740 for the Symptom Checklist subscale and 0.794 for the Symptom Severity subscale. Acording to Cicchetti (1994) Compulsive Scale (López Nicolás et al, 2021;López-Pina et al, 2015;Núñez-Núñez et al, 2022;Rubio-Aparicio et al, 2020;Sánchez-Meca et al, 2011, we see that they have similar or slightly better psychometric properties. Nonetheless, we want to again emphasize that the FOCI and C-FOCI are the only OCD scales that briefly examine both OCD symptoms and their severity, while also being brief, simple, and self-reported.…”
Section: Discussionmentioning
confidence: 60%
“…Acording to Cicchetti ( 1994 ), these values can be considered as good (FOCI) and fair (C‐FOCI) reliability coefficients, respectively. If we compare these values to those obtained in other RG meta‐analyses of other OCD scales such as the Y‐BOCS, the original Padua Inventory (PI) and their two revisions (the Padua Inventory Revision [PI–R], and the Padua Inventory–Washington State University Revision [PI–WSUR]), the Maudsley Obsessional Compulsive Inventory and the Dimensional Obsessive‐Compulsive Scale (López Nicolás et al, 2021 ; López‐Pina et al, 2015 ; Núñez‐Núñez et al, 2022 ; Rubio‐Aparicio et al, 2020 ; Sánchez‐Meca et al, 2011 , 2017 ), we see that they have similar or slightly better psychometric properties. Nonetheless, we want to again emphasize that the FOCI and C‐FOCI are the only OCD scales that briefly examine both OCD symptoms and their severity, while also being brief, simple, and self‐reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Padua Inventory-Revised (PI-R) is a widely applied instrument to measure OCSs in clinical and nonclinical samples (Núñez-Núñez et al, 2022). It was developed by Sanavio (1988) and revised by Van Oppen (1992) to measure the common subtypes of OCSs.…”
Section: Methodsmentioning
confidence: 99%
“…100 The purpose of a reliability meta-analysis is to estimate the mean reliability and look for moderator variables that can account for part of the variance in the scale. 101 Also, some studies evaluated the levels of PS among burns patients and different values were reported. 96,102,103 The averages of total PS and factors were not estimated in the review study.…”
Section: Introductionmentioning
confidence: 99%
“…The alpha coefficient value above 0.70 was considered acceptable for the scale 100 . The purpose of a reliability meta‐analysis is to estimate the mean reliability and look for moderator variables that can account for part of the variance in the scale 101 . Also, some studies evaluated the levels of PS among burns patients and different values were reported 96,102,103 .…”
Section: Introductionmentioning
confidence: 99%